18+93=3x

Simple and best practice solution for 18+93=3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18+93=3x equation:



18+93=3x
We move all terms to the left:
18+93-(3x)=0
We add all the numbers together, and all the variables
-3x+111=0
We move all terms containing x to the left, all other terms to the right
-3x=-111
x=-111/-3
x=+37

See similar equations:

| -18h+12h=6 | | -14+18t=17t | | 2.55=100i/4775000 | | 2w-12=-2w+16 | | 2-m=-7 | | 3(4x-9)=11x-16 | | 5(3n+2)=6(6n+3)4 | | 18=m/12 | | 16d-15d-1=10 | | -7+16f=8+17f | | 3j-j-j+2j-2j=16 | | 7t-4t+1=19 | | 55-6x=19+12x | | -2(u+11)+15=3 | | 3r-r-1=13 | | 4z-2z-2=16 | | -1(5x+8)+12+5x=4 | | -5-2x=-2x-5 | | -8y-10y=-18 | | 3t+-7t=20 | | 2(3n+3=7(3n+3)+7 | | 2x+18(x-2)=4 | | -3v-16=-v | | -18x+15x-90=3x+12x-+60 | | -10+3f=5f=6 | | 9=-3(m-20) | | -12h+9h=3 | | -3(p-20)=15 | | -16-15g=-11g | | 3(6c-1)-12=16c+3 | | 17a-14a-3a+a=4 | | -4(4x+3)=-36-8x |

Equations solver categories